(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Digital currencies, including central bank digital currencies (CBDCs) and cryptocurrencies, are changing the global financial structures through efficiency, financial inclusion, and financial policy challenges. This article looks at their transformative potential in a comparative perspective between advanced and emerging economies. Using figures published by the International Monetary Fund (IMF), Bank for International Settlement (BIS), and World Bank, some of the most important conclusions are that more than 90% of central banks are discussing or testing CBDCs, with emerging markets as the most adopting to lower cash dependency and transaction expenses. Quantitative data show that in India, digital rupee circulation increased by 334 per cent year-on-year to half a billion dollars and around the world, cryptocurrency usage by adults was 12.4 per cent of those with internet access. Such innovations could increase GDP growth by 1-2 percent in developing economies due to better transactions and access to finance, but they also create risks for financial stability, like people moving away from traditional banks and the danger of online security attacks. The relevance of policy is based on the fact that harmonized international regulations are required to reduce the cross-border risks and leverage inclusiveness in growth. The discussion highlights that there should be a middle ground by promoting sound structures that would promote fair distributions of benefits amid geopolitical conflicts.